Development of Ludo Game Based Android as Learning Media on Reduction and Oxidation Reaction Material - Iswendi, Iswendi; Iryani, Iryani; Sari, Indah Fedya; Ningsih, Puji Aptriyani Anggelia (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2024)
The era revolution 4.0 is an era of digitalization especially in education. Exercise that was initially conventionally using paper does not always provide opportunities high interest students because students are bored using paper. One of innovations is developing a chemistry ludo game as an alternative exercise model. The goal is develop and determine the level validity, practicality, and effectiveness. This type is the Plomp model Educational Design Research with 3 stages, namely initial, prototype, and assessment stage. The research instruments are questionnaires and test instruments. Validity data were analyzed using Aiken`s V and all validation aspects were above 0.80 so the results of content, construction and media validation showed a valid category, practicality data were analyzed using percentage formula with a result of 90% in practical category, and effectiveness using N-Gain with the results experimental class of 0.79 high criteria, while the control class only 0.47 moderate criteria. Hypothesis namely the tcount 7.84527 and ttable of 0.05 obtained 1.668 so the learning outcomes of the experimental class higher. So, the ludo game is valid, practical, and effective. So that this media can be used for educators as an alternative to providing exercise using fun technology for students.